Risk factors of limited joint mobility in type 1 diabetic adolescents: a two-center experience in Iraq (Medical Journal of Indonesia, 2022)
BACKGROUND Limited joint mobility (LJM) is the most common joint-related complications in patients with diabetes mellitus (DM) and indicates the presence of microvascular complications. This study aimed to assess the frequency of LJM among adolescents with type 1 DM (T1DM), its risk factors, and the other microangiopathies. METHODS In this cross-sectional study, 75 patients (adolescents between 10 and 17 years old) with T1DM were assessed for hand joint mobility using a prayer sign test. It was carried out from January 15 to June 1, 2022 in Baghdad city, Iraq. The patients’ height, body mass index, blood pressure, glycated hemoglobin, and low-density lipoprotein (LDL) were recorded. Only 44 subjects were screened for diabetic nephropathy and 64 for diabetic retinopathy based on the eligibility criteria by the American Diabetes Association guidelines. RESULTS Mean age was 13.60 (1.85) years, with a mean diabetes duration of 5.61 (2.87) years. LJM was found in 18 patients (24%). It was associated with a longer duration of diabetes (p<0.001), high LDL level (p = 0.012), diabetic nephropathy (p = 0.04), and diabetic retinopathy (p<0.001). CONCLUSIONS The proportion of LJM was high among adolescents with T1DM, especially in those with a long duration of DM. It was associated with high LDL levels and diabetic microangiopathies (nephropathy and retinopathy).